Transcription factor ZFP38 is essential for meiosis prophase I in male mice. Issue 5 (November 2016) - Yan, Zechen; Fan, Dandan; Meng, Qingjun; Yang, Jinjian; Zhao, Wei; Guo, Fei; Song, Dongjian; Guo, Ruiming; Sun, Ke; Wang, Jiaxiang
Abstract : The production of haploid gametes by meiosis is a cornerstone of sexual reproduction and maintenance of genome integrity. Zfp38 mRNA is expressed in spermatocytes, indicating that transcription factor ZFP38 has the potential to regulate transcription during meiosis. In this study, we generated Zfp38 conditional knockout mice ( Zfp38 flox/flox, Stra8 -Cre, hereafter called Zfp38 cKO) and found that spermatogenesis did not progress beyond meiosis prophase I in Zfp38 cKO mice. Using a chromosomal spread technique, we observed that Zfp38 cKO spermatocytes exhibited a failure in chromosomal synapsis observed by SYCP1/SYCP3 double staining. Progression of DNA double-strand breaks (DSB) repair is disrupted in Zfp38 cKO spermatocytes, as revealed by γ-H2AX, RAD51 and MLH1 staining. Furthermore, the mRNA and protein levels of DSB repair enzymes and factors that guide their loading onto sites of DSBs, such as RAD51, DMC1, RAD51, TEX15 and PALB2, were significantly reduced in Zfp38 cKO spermatocytes. Taken together, our data suggest that ZFP38 is critical for the chromosomal synapsis and DSB repairs partially via its regulation of DSB repair-associated protein expression during meiotic progression in mouse.